The Mapping of Dakwah Potencies in Supporting Rejang Lebong to be a Religious Regency - Hariyatoni Hariyatoni; Hasep Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Islam is a religion of da’wah, which is a religion that advocates to followers to invite all people to believe, charity, create and organize life in accordance with Islamic values. Today, da'wah as a noble task in its implementation has not been managed professionally and measurable. On the other hand da'i has not been able to be a change agent as the ideals of Islam is rahmatan lil'âlamîn. Consequently the position of da'wah is less desirable because it has not been able to give a significant influence for the progress of the people. Therefore, comprehensive assessment and mapping of the strengths, weaknesses, opportunities and challenges of da'wah are required. This study offers the argument that a comprehensive mapping of the matter and then accompanied by professional planning and implementation of da'wah, professionally so the da'wah will be able to give influence and be a solution to various problems of people life in the current era of globalization.